Peran Guru Dalam Menginternalisasi Nilai-Nilai Tauhid Di Tengah Pengaruh Budaya Modern Pada Anak Usia Dini - Raniyah, Qaulan (AUD Cendekia: Journal of Islamic Early Childhood Education, 2024)
This study aims to analyze the role of teachers in internalizing the values of tawhid amid the influence of modern culture in early childhood education, with a case study conducted at TK Yayasan Pendidikan Islam. Using a qualitative approach with a case study design, this research explores teachers’ experiences and strategies in instilling the value of the Oneness of Allah in children living in a digital and consumerist era. The findings reveal that teachers play a central role as spiritual educators, moral exemplars (uswah hasanah), and mediators between school and family. The main challenges encountered include the penetration of digital culture, hedonistic tendencies, and weak continuity of religious education at home. To address these challenges, teachers employ three primary strategies: modeling and habituation of religious practices, contextualizing tawhid values through modern learning media, and fostering collaboration with parents. This approach demonstrates teachers’ adaptive ability to integrate technology without losing the essence of Islamic values. The study contributes to the theoretical development of Islamic early childhood education by offering a new paradigm of tawhid internalization that is contextual, integrative, and relevant to the challenges of modernity. Practically, the results of this study can serve as a reference for Islamic kindergartens in strengthening spiritually grounded learning programs that remain adaptive to contemporary developments.